2011
DOI: 10.1073/pnas.1009069108
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of melanomas by targeted elimination of a minor subset of tumor cells

Abstract: Proceeding on the assumption that all cancer cells have equal malignant capacities, current regimens in cancer therapy attempt to eradicate all malignant cells of a tumor lesion. Using in vivo targeting of tumor cell subsets, we demonstrate that selective elimination of a definite, minor tumor cell subpopulation is particularly effective in eradicating established melanoma lesions irrespective of the bulk of cancer cells. Tumor cell subsets were specifically eliminated in a tumor lesion by adoptive transfer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 25 publications
0
101
0
4
Order By: Relevance
“…A CD20 + sejtek viszont nem mutattak nagyobb tumoriniciátor kapacitást a CD20 -adherens populációkhoz képest, ráadásul differenciációs képességük is idővel csökkent. Ugyanakkor a CD20 ellen kifejlesztett immunsejt- [39] és antitest-terápia [40] ígéretes eredményeket hozott a melanomasejtek progresszió-jának megakadályozásában. Mindez arra utal, hogy a CD20 + melanomasejteknek komoly jelentősége van a melanomák heterogenitásában és terjedésében.…”
Section: őSsejteredetű Markerek Melanomábanunclassified
See 1 more Smart Citation
“…A CD20 + sejtek viszont nem mutattak nagyobb tumoriniciátor kapacitást a CD20 -adherens populációkhoz képest, ráadásul differenciációs képességük is idővel csökkent. Ugyanakkor a CD20 ellen kifejlesztett immunsejt- [39] és antitest-terápia [40] ígéretes eredményeket hozott a melanomasejtek progresszió-jának megakadályozásában. Mindez arra utal, hogy a CD20 + melanomasejteknek komoly jelentősége van a melanomák heterogenitásában és terjedésében.…”
Section: őSsejteredetű Markerek Melanomábanunclassified
“…NSG-egerekbe xenotranszplantált melanomasejtek által létrehozott tumorokat sikeresen eradikáltak a CD20 ellen kifejlesztett citotoxikus T-sejtekkel [39]. A T-sejteket olyan kimérareceptorral transzfektálták, amelynek extracelluláris doménje egy anti-CD20 antitest antigénkötő (Fab) régióját hordozta, citoplazmatikus doménje pedig a T-sejtek aktiválódásá-ért felelős CD3ζ intracelluláris doménjét tartalmazta.…”
Section: Terápiás Stratégiák Melanoma-őssejtmarkerekkel Szembenunclassified
“…83 Targeting a minor subset of tumour cells, such as cancer stem cells, may obviate the requirement for extensive T cell recruitment. 84,85 Innovative cell delivery systems such as focused ultrasound may also lead to improvements in this area. 86 Investigation into a combination of targeted and immune therapies are warranted, for example, a combination of CAR T cell therapy with immunomodulatory protocols to tackle the immunosuppressive microenvironment induced by solid tumours.…”
Section: Future For Car T Cell Therapymentioning
confidence: 99%
“…[57] Deng et al, [58] for instance, demonstrated that CAR T cell therapy could inhibit tumor growth of highly metastatic prostate cancer that expresses low levels of EpCAM. Other CSC-targeting adoptive T cell therapies include CAR T cells which bind to a CSCspecific N-glycosylation-dependent epitope of CD133, [59] high-molecular weight melanoma associated antigen or chondroitin sulfate proteoglycan 4-specific CAR T cells that were reported to specifically eliminate melanoma with a CSC phenotype, [60,61] and epidermal growth factor receptor variant III (EGFRvIII) specific CAR T cells which target glioma SCs. [62] Cells in the tumor microenvironment was also found to express several negative immune regulators such as programmed cell death 1(PD-1) and its ligand (PD-L1), cytotoxic T lymphocyte associated 4 (CTLA-4), and transforming growth factor β (TGF-β).…”
Section: Enhancing Immune Responsesmentioning
confidence: 99%